Emerging Technologies to Promote Fans Interaction in Football Events: A Systematic Review - Francisco Martins; Cíntia França; Pedro Paixão; Diogo V. Martinho; Pedro Campos; Bruna Gouveia; Helder Lopes; Andreas Ihle; Eduardo Marques; Élvio Rúbio Gouveia (Advances in Human-Computer Interaction)
As the digital revolution continues to take hold in contemporary society, new technology and communications networks have provided football with new possibilities and prospects for expansion. This study provides an assessment of the published research regarding innovative digital tools designed to increase the interactivity of fans when watching a football match, regardless of whether they do it at home or at the stadium. A systematic review of the literature was performed, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. The search was conducted in the PubMed, Web of Science, and Scopus databases. The final sample included eleven studies for analysis. Overall, the investigations that structure this review seem to be in the early stages of their development, with eight of them making tests with the target audience and the other three still in protocol development processes. Six studies concluded that fans had positive and exciting experiences using mobile applications or interactive systems. Two studies showed promising results in the area of football fans’ health, and only one study showed some difficulties for fans using an ad hoc network in the stadium. Adding personal information, fan interaction systems, specific information about the players and the teams’ tactical strategies, and interactive fan voting seem to be important elements for designing a successful interactive tool that contributes to increasing fans’ enthusiasm during football matches.